Analisis Tingkat Kepuasan Pengguna Layanan Tiktok Shop Menggunakan System Usability Scale (SUS) - Dwi Rosa Indah; Dedi Kurniawan; Ariansyah Saputra; Windy Indrianti; Sanjaya , M. Rudi (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2023)
TikTok Shop is a shopping feature developed from the TikTok application which was launched in April 2021. Currently, the TikTok platform occupies the largest number of users in the world with a total of more than 2 billion downloads. The purpose of this research is to determine the level of user satisfaction in accessing and using the Tiktok Application towards the Tiktok Shop service. Therefore, it is one of the aspects that is quite important in knowing and assessing the availability and completeness of information needed by users on the System. So, from this problem, researchers analyse the User Satisfaction Level of Tiktok Shop Service Using the System Useability Scale (SUS) Method, which with this method can analyse the satisfaction level data for users who use the Tiktok application, the SUS method uses questionnaire data to determine the level of user satisfaction with the Tiktok application. Which is where researchers have collected 310 respondents to determine the score results to determine the level of satisfaction of Tiktok application users. And from the results that have been obtained, it is known that the calculation of the average SUS score on the Tiktok Shop application is 74.57 which in general can be categorised as "Acceptable". With the grade scale C range, but the user Adjective Rating range in the Tiktok Shop application is classified as the "Good" category where the results of the application of SUS in this study are in accordance with the criteria in the System Useability Scale (SUS) method.